Fiscal Sustainability of Local Governments in the Visegrad Group Countries - Tomasz Uryszek (Entrepreneurial Business and Economics Review)
Objective: The main goal of the article is to assess the level of fiscal sustainability at the local government level in the Visegrad Group (V4) economies. Research Design & Methods: Two different methods of fiscal sustainability measures were used in the article to verify whether the local government deficit is sustainable: estimations of the no-Ponzi conditions, and calculations of the threshold primary balance. The research period covered the years 2001-2016. Data were taken from the Eurostat database. Findings: Three out of four V4 countries met the initial no-Ponzi condition. The sums of discounted primary balances of their local governments were positive (Poland was the only exception). However, those sums were insufficient to cover the initial debt volume. It was possible in Hungary only. The Ponzi scheme was significantly reduced during the recovery time after the financial crisis of 2008-2009. Implications & Recommendations: Generally, all the countries showed the potential to produce primary surpluses at the local level and they have been generally able to stabilise the local debt to GDP ratio. However, these surpluses in the Czech Republic, Slovakia and Poland were insufficient to cover the initial level of debt. Especially Poland should try to generate higher primary local surpluses to avoid the Ponzi scheme and increase the level of fiscal sustainability at the local government level in the future. Contribution & Value Added: The originality of this work lies in using the Ponzi scheme and the values of the threshold primary gap to assess the fiscal sustainability of local government levels in the Visegrad Group Economies.